2020
DOI: 10.1136/rapm-2020-101547
|View full text |Cite
|
Sign up to set email alerts
|

Sharing the pain: an observational analysis of Twitter and pain in Ireland

Abstract: IntroductionStudies involving Twitter and chronic pain can provide highly valuable patient-generated information. The aim of this paper was to examine pain-related tweets in Ireland over a 2-week period from 22 June 2017 to 5 July 2017 using pain-related keywords. We wished to identify Twitter user gender profile; most common discussion topics; sentiment analysis; and dissemination of tweets.MethodsA third-party data analytics company conducted a Twitter social media analysis over a randomly chosen 14-day peri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 46 publications
2
20
0
2
Order By: Relevance
“…9 4) Mullins et al have studied topics and keywords in a randomly chosen 14-day periods in 2017 in Ireland. 10 5) Finally, in a survey of 20,301 tweets from September 30, 2019 to January 14, 2020 we showed that topics of “#CBD,” “#cannabis,” as well as “#chronicillness,” “#chronic pain” and “#spoonie” were some of the most commonly tweeted hashtags. 11…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…9 4) Mullins et al have studied topics and keywords in a randomly chosen 14-day periods in 2017 in Ireland. 10 5) Finally, in a survey of 20,301 tweets from September 30, 2019 to January 14, 2020 we showed that topics of “#CBD,” “#cannabis,” as well as “#chronicillness,” “#chronic pain” and “#spoonie” were some of the most commonly tweeted hashtags. 11…”
Section: Discussionmentioning
confidence: 92%
“…Alternative medicine and health strategies such as #yoga is present in May and #acupuncture, #chiropractic is present in June. Advocacy topics such as #mham (Rank 2), #mham2020 (Rank 4), #shadesformigraine (Rank 5), #cmaware (rank7), #rallyagainstchronicmigraine (13), #migraineawareness (10) are the most commonly hashtags presented in June; #cmaware, #mham, #rallyagainstchronicmigraine, #migraineawareness were ranked at 3, 6, 12, 19, respectively in May.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mullins и соавт. [11] провели анализ социальной сети Twitter и включили в поиск несколько релевантных ключевых слов по проблеме боли. Только в течение 14-дневного периода был обнаружен 941 твит от 715 авторов.…”
unclassified